Indicators of sailing performance in youth dinghy sailing - Callewaert, M.; Boone, J.; Celie, B.; De Clercq, D.; Bourgois, J. G. (European Journal of Sport Science, 2015)
This study aimed to determine indicators of sailing performance in 2 (age) groups of youth sailors by investigating the anthropometric, physical and motor coordination differences and factors discriminating between elite and non-elite male optimist sailors and young dynamic hikers. Anthropometric measurements from 23 optimist sailors (mean ± SD age = 12.3 ± 1.4 years) and 24 dynamic youth hikers (i.e. Laser 4.7, Laser radial and Europe sailors <18 years who have to sail the boat in a very dynamic manner, due to a high sailor to yacht weight ratio) (mean ± SD age = 16.5 ± 1.6 years) were conducted. They performed a physical fitness test battery (EUROFIT), motor coordination test battery (Körperkoordinationstest für Kinder) and the Bucket test. Both groups of sailors were divided into two subgroups (i.e. elites and non-elites) based on sailing expertise. The significant differences, taking biological maturation into account and factors discriminating between elite and non-elite optimist sailors and dynamic hikers were explored by means of multivariate analysis of covariance and discriminant analysis, respectively. The main results indicated that 100.0% of elite optimist sailors and 88.9% of elite dynamic hikers could be correctly classified by means of two motor coordination tests (i.e. side step and side jump) and Bucket test, respectively. As such, strength- and speed-oriented motor coordination and isometric knee-extension strength endurance can be identified as indicators of sailing performance in young optimist and dynamic youth sailors, respectively. Therefore, we emphasise the importance of motor coordination skill training in optimist sailors (<15 years) and maximum strength training later on (>15 years) in order to increase their isometric knee-extension strength endurance.